VD_FINDINFO HC / 2013 / 155 vom 27. Februar 2013 - VD Tribunal cantonal (2013)
LIMITATIONEN GÉNÉRAL, VENTE D'IMMEUBLE, DROIT DE PRÉEMPTION, COPROPRIÉTÉ | 682 al. 1 CC, 960 al. 1 ch. 1 CC, 960 al. 2 CC, 49 al. 1 LDFR